2009
DOI: 10.1124/jpet.109.151746
|View full text |Cite
|
Sign up to set email alerts
|

As in Humans, Pregnancy Increases the Clearance of the Protease Inhibitor Nelfinavir in the Nonhuman Primate Macaca nemestrina

Abstract: The apparent oral clearance of protease inhibitors (PIs) is increased in pregnant women. Although this phenomenon is reproduced in the mouse, because of the multiplicity of mouse cytochrome P450 isoforms, lack of information on their substrate and inhibitor selectivity, and lack of reagents (e.g., antibodies, purified protein), it is difficult to study the mechanistic basis of this phenomenon in this animal model. To investigate the mechanistic basis of this phenomenon in a more representative model, the nonhu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…For this reason, we began studies in a more representative animal model that is genetically and physiologically closer to humans, the pregnant non-human primate, Macaca nemestrina (pig-tailed macaque). We confirmed that oral and systemic clearance of a model PI, nelfinavir, was increased in the pregnant M. nemestrina (Zhang et al, 2009). In addition, in vitro studies with hepatic and intestinal S-9 fractions obtained from pregnant and postpartum animals suggested that the increased oral clearance of NFV was caused by increased hepatic but not intestinal CYP3A activity.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…For this reason, we began studies in a more representative animal model that is genetically and physiologically closer to humans, the pregnant non-human primate, Macaca nemestrina (pig-tailed macaque). We confirmed that oral and systemic clearance of a model PI, nelfinavir, was increased in the pregnant M. nemestrina (Zhang et al, 2009). In addition, in vitro studies with hepatic and intestinal S-9 fractions obtained from pregnant and postpartum animals suggested that the increased oral clearance of NFV was caused by increased hepatic but not intestinal CYP3A activity.…”
supporting
confidence: 70%
“…Four pregnant (antepartum, AP 73-118 day; term is ϳ167 days) and four nonpregnant (postpartum, PP 61-130 day) macaques (M. nemestrina, 7.0 -12 years, 6.5-10 kg) were studied. The nelfinavir pharmacokinetic studies that we reported previously were also conducted in these animals during the same pregnancies (Zhang et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations